2000
DOI: 10.1055/s-2000-3834
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Supraphysiological Doses of Anabolic Androgenic Steroids on Collagen Metabolism

Abstract: We examined the effect of supraphysiological doses of anabolic androgenic steroids (AAS) on collagen metabolism and whether the changes reflect the alterations in muscle, bone, and tendon collagen metabolism, possibly in a tissue-specific manner. Serum carboxyterminal propeptide of type I procollagen (PICP), carboxyterminal telopeptide of type I collagen (ICTP), aminoterminal propeptide of type III procollagen (PIIINP), urine hydroxylysylpyridinoline (HP), and lysylpyridinoline (LP) as well as urine creatinine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
22
0
5

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 23 publications
(32 reference statements)
2
22
0
5
Order By: Relevance
“…Previous studies have also demonstrated that administration of AAS inhibits the activity of MMPs, possibly impairing tendon remodeling (Dheda et al 2004;Marqueti et al 2010). However, the effects of AAS on collagen gene expression are poorly understood, although AAS may be associated with tendon dysfunction and fibrosis (Pärssinen et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have also demonstrated that administration of AAS inhibits the activity of MMPs, possibly impairing tendon remodeling (Dheda et al 2004;Marqueti et al 2010). However, the effects of AAS on collagen gene expression are poorly understood, although AAS may be associated with tendon dysfunction and fibrosis (Pärssinen et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…However, the use of anabolic-androgenic steroids (AAS) strongly inhibits this turnover (Marqueti et al 2006). Supraphysiological doses of AAS result in altered muscle, bone and tendon metabolism (Pärssinen et al 2000). AAS are used as ergogenic aids by athletes and nonathletes to enhance performance by increasing muscle size and strength.…”
Section: Introductionmentioning
confidence: 99%
“…High and multi-doses of AAS used for athletic enhancement can lead to serious and irreversible organ damage (Maravelias et al 2005). The combination of AAS and exercise induce deleterious alterations in tendon such as the presence of displastic Wbrils, with clear disruption of the Wbril interface (Michna 1986(Michna , 1987Miles et al 1992;Inhofe et al 1995;Mottram and George 2000;Pärssinen et al 2000;Bahrke and Yesalis 2004). This structural alteration results in increase of tendon stiVness and loss of elasticity, so that tendon becomes more prone to rupture (Wood et al 1988;Miles et al 1992;Inhofe et al 1995;Laseter and Russel 1991;Evans 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Case reports on hard atherosclerotic endpoints (sudden cardiac death, MI or stroke) comprise young AAS abusers without preexistent cardiac risk factors, suggesting that a high AAS dose imposes additional independent risk to conventional cardiovascular risk factors. Parssinen et al [10] reported a more than four times higher incidence of early death in professional athletes abusing AAS compared to the age-and sex-matched general population, in a 12-years prospective observation.…”
Section: Introductionmentioning
confidence: 98%